Carneiro Leão and the Reform of Foreign Languages in Brazil (1930-1934) - Jonathas de Paula Chaguri; Maria Cristina Gomes Machado (Universidade Federal do Rio Grande do Sul, 2019)
Carneiro Leão's proposal for a reform in the teaching of foreign languagesat secondary school level, at the Colégio D. Pedro II, between 1930 and 1934, is analyzed. Results show that Carneiro Leão was in favor of a foreign language reform featuring an active and dynamic learning process within the context of engagement in the ideals of an active school. In fact, Carneiro Leão gave a new identity to the study of languages, ensuring a convincingly practical and useful teaching, without the disassociation of the characteristics of the Humanities for people who needed training for production means in the country's commerce and industry.